Cell Growth - Vikas, Biba; Fasullo, Michael (IntechOpen, 2020)
This book on cell growth is the ideal resource for a scientist who wishes to learn more about cell growth topics. It provides information on plant growth hormones, kinetic studies on cell growth, growth of fungal cells and production, cell growth measurement, ion homeostasis response to nutrient deficiency stress in plants, intracellular lipid homeostasis in eukaryotes, and cell-based assays in cancer research. Each topic begins with a summary of the essential facts. Chapters were carefully edited to maintain consistent use of terminology and approach of covering topics in a uniform, systematic format.